Density-dependent solute transport in a layered hyporheic zone. (August 2020) - Jiang, Qihao; Jin, Guangqiu; Tang, Hongwu; Shen, Chengji; Cheraghi, Mohsen; Xu, Junzeng; Li, Ling; Barry, D.A.
Highlights: Flume experiments and numerical models of solute transport in a layered bedform were conducted. A combination of mechanisms produces irregular spatial patterns of solute transport in the hyporheic zone. Disconnected transportation was formed under a discontinuous low-permeability layer. Abstract: Hyporheic exchange is affected by bedform geometry, which induces complex flow paths within the bedform. Additional factors that influence flow and solute transport in the hyporheic zone are layered profile sediments and density-driven flow. This study explored the combined effects of these factors on hyporheic exchange through laboratory experiments and numerical simulations involving infiltrating solute displacing less-dense resident water in a layered bedform with a low permeability layer (LPL). The bedform consisted of three horizontal layers, in which the hydraulic conductivity of the middle layer (LPL) was less than that of the top (TL) and bottom layers (BL). The results demonstrated that a previously unexplored combination of mechanisms (density effects and layered bedform) produces irregular spatial patterns of solute transport in the hyporheic zone. For instance, the width of solute plume within the bottom layers becomes narrowed compared with tracer transport. With increasing density contrast between infiltrating solute and resident water, the solute plume becomes much narrower, forming fingers. Numerical modeling further shows that the hydraulic conductivity contrast (HCC) and relative thickness (RT) of the hyporheic zone layers also affect the spatial solute transport patterns. As the hydraulic conductivity contrast or relative thickness increases, the plume becomes much narrower. Horizontal ambient flow (HAF) dominated in the bottom layers, and lateral solute spreading and mixing intensified with a higher hydraulic conductivity contrast and relative thickness. Furthermore, the vertical solute plume was detached by the horizontal ambient flow in the bottom layers with a discontinuous low permeability layer, forming a discontinuous zone of vertical solute transport. Graphical abstract: Image, graphical abstract